Synthetic cannabinoid use among high school seniors - Palamar, J.; Barratt, Monica; Coney, L.; Martins, S. (American Academy of Pediatrics, 2017)
© 2017 by the American Academy of Pediatrics. OBJECTIVES: In this study, we examined the prevalence and correlates of current synthetic cannabinoid (SC) use among high school seniors in the United States. METHODS: Monitoring the Future, an annual nationally representative survey of high school seniors, began querying current (30-day) SC use in 2014. Data were examined from the 2 most recent cohorts (2014-2015; N = 7805). Prevalence of self-reported use was examined and differences in demographics and recency and frequency of other drug use was compared between current marijuana-only users and current SC (plus marijuana) users using X 2 and generalized linear model using Poisson. RESULTS: We found that 2.9% of students reported current SC use; 1.4% of students (49.7% of users) reported using SCs on ≥3 days in the past month. SC users were more likely to report more recent (and often more frequent) use of lysergic acid diethylamide, cocaine, heroin, and/or nonmedical use of opioids compared with marijuana-only users. Compared with current marijuana-only users, SC users were more likely to report lower parent education (P < .05) and current use of a higher number of illegal drugs other than marijuana (Ps < .001). Students using SCs ≥10 times in the past month were more likely to be boys, frequent marijuana users (Ps < .01), African American, and users of multiple other illegal drugs (Ps < .001). CONCLUSIONS: SC use is typically part of a repertoire of polydrug use, and polydrug use is less prevalent among marijuana-only users. Current SC users are at risk for poisoning from use of the newest generation of SCs and from concurrent drug use.